Ways of Celebrating Ram’s Birth: Ramayana Week in Greater Durban - Richman, Paula (Religions of South Asia, 2010)
Hindu descendants of Indian indentured labourers, who arrived in colonial Natal between 1860 and 1910, celebrate Ram Navami (Ram’s birth) today in Greater Durban, South Africa, in diverse ways related to the Indian regions from which their ancestors came and their subsequent history after they settled locally. Hindi-speaking Hindus focus on exegesis of Ramcaritmanas, a text-centred practice, while Telugu-speaking Hindus celebrate with bhajans by composers such as Tyagaraja and Bhadrachala Ramdas, a song-centred practice. This contrast in language and style shows how religious practice retains the imprint of the area of their ancestors’ origin. In contrast, that worshippers come from far distances to join the unique celebration of Ram in his cradle at the Durban Hindu Temple, founded in 1901 across from the Railway Barracks where large numbers of Indians lived, reflects their dispersal from downtown Durban due to the Group Areas Act during apartheid. A Ram-centered dance drama based on Valmiki’s Ramayana, which received funding from the National Arts Council, suggests that at times the post-apartheid state classifies Hindu dance drama as a historically disadvantaged art form. The four examples show how the circumstances of indenture and the effects of apartheid have shaped today’s observance of Ram Navami in Durban.